(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine and determine the legal force of information technology-based money lending agreements. The research method used is the normative legal research method, namely legal research that uses secondary data sources. Namely, secondary data sources in the form of or thoughts of experts or experts who study in the form of books, journals, such as literature books on the basics of agreement law and laws and regulations. The results of the study obtained are that Information Technology-Based Money Lending Services (Fintech Lending) are an innovation in the financial sector that allows online lending transactions using an electronic system. Online loan agreements are regulated by the Financial Services Authority Regulation Number 10/POJK.05/2022. This agreement is legally valid and has legal force as long as it meets the valid requirements according to Article 1320 of the Civil Code, namely agreement, ability, a certain thing, and a lawful cause. The resolution of disputes in information technology-based loan agreements when a default occurs can be carried out through litigation or non-litigation. The litigation path is usually referred to as the path taken in court, while the non-litigation path is through the Alternative Dispute Resolution Institution (LAPS), which can be taken through mediation, arbitration, and binding opinions. The recommendation from this study is to provide education to users about the terms and conditions of the agreement, focus on the validity and certainty of law, and strengthen regulations on personal data security and dispute resolution mechanisms. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menentukan kekuatan hukum perjanjian pinjam meminjam uang berbasis teknologi informasi. Metode penelitian yang dipakai ialah metode penelitian hukum normatif yaitu penelitian hukum yang mempergunakan sumber data sekunder. Yaitu sumber data sekunder berupa atau pikiran para pakar atau akhli yang mempelajari dalan bentuk buku, jurnal, seperti buku literatur tentang dasar-dasar hukum perjanjian serta peraturan perundang-undangan. Hasil penelitian yang diperoleh yakni Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi (Fintech Lending) adalah inovasi di bidang keuangan yang memungkinkan transaksi pinjam meminjam secara online menggunakan sistem elektronik. Perjanjian pinjaman online diatur oleh Peraturan Otoritas Jasa Keuangan Nomor 10/POJK.05/2022. Perjanjian ini sah secara hukum dan memiliki kekuatan hukum selama memenuhi syarat sah sesuai Pasal 1320 KUHPerdata, yaitu kesepakatan, kecakapan, suatu hal tertentu, dan suatu sebab yang halal. Adapun penyelesaian sengketa dalam perjanjian pinjam meminjam berbasis teknologi informasi ketika terjadi wanprestasi dapat dilakukan melalui jalur litigasi maupun non-litigasi. Jalur litigasi biasa disebut dengan jalur yang ditempuh di dalam pengadilan adapun Jalur non litigasi melalui Lembaga Alternatif Penyelesaian Sengketa (LAPS) yang diantaranya dapat ditempuh dengan mediasi, arbitrase, dan pendapat mengikat. Rekomendasi dari penelitian ini adalah memberikan edukasi kepada pengguna tentang syarat dan ketentuan perjanjian, fokus kepada validitas dan kepastian hukum serta memperkuat regulasi tentang keamanan data pribadi serta mekanisme penyelesaian sengketa.